Educating in the Arts
XXII, 358 p.
Keywords: Written by leaders in a wide range of creative fields and from all corners of the Asian region, this collection of essays presents arts and education programs which reflect traditional and contemporary practices. The volume brings together researchers, practitioners, educators, children and young people with shared interests in the arts and activities that cross disciplinary divisions and aims to encourage the use of the arts in developing international understanding, celebrating cultural diversity, building cultural bridges and creating cross-cultural dialogue throughout the Asian region. This book arose out of the need to promote not only arts and educational practices; but also the research and evaluations being achieved in the field. Writing about their own practical experiences, the authors explore linkages between creativity and discipline; social organisation and individual expression and how inventiveness and economic productivity are inextricably linked.